Light Deflection in Massive Dyonic Black Holes (Global Journal of Computer Science and Technology, 2024)
Following Rindler-Ishak method 1 we study the bending of light around general form of dyonic black holes in massive gravity 2 We show that when the Schwarzschild-de Sitter geometry is taken into account does indeed contribute to the bending of light